2013
DOI: 10.1186/1471-2369-14-46
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of chronic kidney disease in patients with type 2 diabetes in Spain: PERCEDIME2 study

Abstract: BakgroundThe objective of this study was to determinate the prevalence of chronic kidney disease (CKD) and the different stages of CKD in patients with type 2 diabetes mellitus (DM2) treated in primary care consults in Spain.MethodsA national cross-sectional study was performed in primary care consults. The following data were collected: demographic and anthropometric information; list of present cardiovascular risk factors (CVRF); previous macrovascular and microvascular disease history; physical examination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
60
8
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(95 citation statements)
references
References 34 publications
(32 reference statements)
22
60
8
5
Order By: Relevance
“…A similar study from US with a sample size comparable to ours, presented a similar CKD prevalence of 43.5% (95% confidence interval: 41.6-45.4) [20]. In PERCEDIME2 study from Spain, the prevalence of CKD was estimated to be 27.9% in 1145 T2DM patients of >40 years of age [21]. Similarly in another study conducted in Thailand, prevalence of CKD stage 3-5 were 27.09 and 25.28% [22].…”
Section: Discussionsupporting
confidence: 79%
“…A similar study from US with a sample size comparable to ours, presented a similar CKD prevalence of 43.5% (95% confidence interval: 41.6-45.4) [20]. In PERCEDIME2 study from Spain, the prevalence of CKD was estimated to be 27.9% in 1145 T2DM patients of >40 years of age [21]. Similarly in another study conducted in Thailand, prevalence of CKD stage 3-5 were 27.09 and 25.28% [22].…”
Section: Discussionsupporting
confidence: 79%
“…The prevalence of CKD reported in this study is higher than that seen in most other reports, but the characteristics of patients in those studies tend to be different from that of our patients and some studies used different definitions for CKD. For example, a study among diabetic patients in primary care practices in Spain reported a CKD prevalence of 27.9%, but while these patients were older than those in this study, the mean duration of diabetes was only nine years compared to 17 years in this study (14). One study among urban community-based participants in China reported a CKD prevalence of 29.6% (15), but another study among participants over 30 years old from 'downtown Shanghai' reported a CKD prevalence of 63.9% (16).…”
Section: Discussioncontrasting
confidence: 74%
“…Diese Definition wurde später durch die klassischen fünf Stadien des natürlichen Krankheitsverlaufes ergänzt: Stadium I, Hyperfiltration mit glomerulärer Hypertrophie und transienter Albuminurie; Stadium II, die ruhige Phase mit Normalisierung der GFR und der Albuminexkretion, begleitet durch Verdickung der glomerulären Basalmembran und eine Mesangialexpansion; Stadium III, inzipiente Nephropathie mit persistierender Mikroalbuminurie; Stadium IV, "overt" Nephropathie mit Verschlechterung der Albuminurie (von Mikrozur Makroalbuminurie) und Retinopathie, Blutdruckverschlechterung und Abnahme der Nierenfunktion; und letztlich Stadium V, mit variablem GFR-Verlust bis zur terminalen Niereninsuffizienz, charakteristischerweise 25-30 Jahre nach Krankheitsbeginn, welches aber aufgrund der hohen Mortalität häufig nicht erreicht wird [16] [17,18], wurde es routinemäßig auch auf Patienten mit DM2 angewandt und war auch noch zuletzt in den Richtlinien der beiden Gesellschaften so verankert [19]. Mittlerweile geht man davon aus, dass mehr als 50 % der Patienten mit DM2 in Langzeitbeobachtungen eine GFR < 60 ml/min ohne vorangehende Albuminurie entwickeln [20][21][22][23] beziehungsweise der Verlauf der Albuminurie nicht mit dem Nierenfunktionsverlust korreliert [24]. Der neue Begriff der "diabetischen Nierenerkrankung" reflektiert die beobachtete strukturelle und klinische Heterogenität sowohl bei DM1 als auch vor allem bei DM2.…”
Section: Definition Der Diabetischen Nierenerkrankungunclassified